The biomechanics of proximal humeral fractures: Injury mechanism and cortical morphology. (August 2019) - Majed, Addie; Thangarajah, Tanujan; Southgate, Dominic FL; Reilly, Peter; Bull, Anthony; Emery, Roger
Background: The aim of this study was to examine the effect of arm position on proximal humerus fracture configuration and to determine whether cortical thinning would predispose to fracture propagation and more complex patterns of injury. Methods: A drop test rig was designed to simulate falls onto an outstretched arm ('parachute reflex'). Thirty-one cadaveric specimens underwent computer tomography scanning and cortical thicknesses mapping. Humeri were fractured according to one of the two injury mechanisms and filmed using a high-speed camera. Anatomical descriptions of the injuries were made. Areas of thinning were measured and correlated with zones of fracture propagation. Results: Direct impact simulation resulted in undisplaced humeral head split fractures in 53% of cases, with the remainder involving disruption to the articular margin and valgus impaction. Alternatively, the 'parachute reflex' predominantly produced shield-type injuries (38%) and displaced greater tuberosity fractures (19%). A strong correlation was demonstrated between cortical thinning and the occurrence of fracture (odds ratio = 7.766, 95% confidence interval from 4.760 to 12.669, p<0.0001). Conclusion: This study has shown that arm position during a fall influences fracture configuration of the proximal humerus. Correlating fracture pattern and mechanism of injury will allow more appropriate fracture reduction techniques to be devised.